Methods for optimization of rotational latency of the inverse loading of trucks on international routes - Azemsha, Sergey (Transport, 2006)
The increase of the efficiency of international car transportation of cargoes is an actual problem. For the solution to delivery problems at present the information systems on the basis of INTERNET‐technology are created, containing information on cargo transportation and available free car transport facilities. This allows somewhat to solve a problem of loading a transport facility in an inverse direction. Thus, there is a task of the acceptance of an optimum decision concerning return loading. In this article the technique is presented, allowing to determine the waiting time of return loading of the vehicle working in any direction at which economic benefit of the performed job will be maximal. First Published Online: 27 Oct 2010